Sintomas osteomusculares e qualidade de vida : uma comparação entre trabalhadores administrativos e de produção de uma indústria agroavícola - Mota, Tamyris Targas (2016)
Work-related musculoskeletal disorders are diseases caused due to musculoskeletal injuries. Moreover, they are the most registered group of occupational diseases in Brazil. Modern industries are favourable environments for the development of musculoskeletal disorders due to the physical and psychosocial demands imposed by the economy. Musculoskeletal symptoms may impairs daily activities, cause work leaves and prejudice quality of life. This study justifies itself based in the need in increasing the investigations about the musculoskeletal symptom manifestation in industry and its interference in quality of life, since the magnitude of the occurrence musculoskeletal disorders in workers is still not well-known in Brazil. Aim: To analyse the prevalence of musculoskeletal symptoms in production and administrative workers in an industry. Objectives: verify the socio-demographic and occupational profile of both studied groups; identify the occurrence of association between pain and socio-demographic and occupational variables; identify the prevalence of pain in the studied body segments; identify the association between intensity and location of pain comparing the two studied groups; identify the associations between quality of life domains and musculoskeletal pain intensity in each assessed body segment. Material and Methods: This was a correlational, descriptive and cross-sectional study that used quantitative analysis. Assessment tools: socio-demographic and occupational assessment tool, Nordic musculoskeletal questionnaire (NMQ), numeric scale of pain to assess the perceived intensity of pain and WHOQOL-bref to assess quality of life. The data collection occurred in an industry of the poultry sector, of a city in the country side of São Paulo state, Brazil. The study was approved by UFSCar Ethics Committee. Results: The sample was composed by 178 workers (154 production workers and 24 administrative workers). Mean age was lower than 30 years in both groups, with prevalence of women and single people only in production sector. The prevalence of musculoskeletal pain was higher than 85% in both sectors. The neck was the body segment with higher prevalence of pain in administrative workers. Production workers reported more intense pain in upper and lower back when compared to administrative workers. Women from production sector had chances increased in 2.9 times in presenting pain when compared to men. The mean value in quality of life domains were moderate, in which the physical domain were more affected in administrative workers when compared to production workers. The correlations between intensity of pain and quality of life domains were not significant in most comparisons. Physical domain presented positive correlations with neck, shoulders and hip pain in production workers. Final considerations: Musculoskeletal pain was highly prevalent in workers from a poultry industry, in both administrative and production sectors. The most affected areas in workers from the administrative sector were neck, lower back and upper back, whilst lower back, shoulders and upper back were the most affected in production workers. Moreover the most prevalent pain in administrative workers was in the neck. The referred pain in almost all body segments were rated as moderate by most of workers. Workers from production sector referred more intense pain in upper and lower back when compared to administrative workers. The mean values in quality of life domains were moderate, and the most impaired domain, in both sectors, was the physical one. The correlations between pain intensity and perceived pain in each body segment compared with quality of life domains in both sectors were not significant in almost all comparisons.